Dukungan Psikososial Bagi Penyintas Bencana Pasca Erupsi Gunung Semeru - Neni Wahyuningtyas; Khofifatu Rohmah Adi; Rahmati Putri Yaniafari; Mochammad Sa'id; M. Gebryna Rizki (Jurnal Pemberdayaan Masyarakat, 2022)
The eruption of Mount Semeru did not only have a physical impact. Victims can experience serious long-term psychological effects and affect their psychological well-being. The psychological impact that is allowed to continue will be permanent and disrupt the survival of disaster survivors. Therefore, psychosocial support is carried out to support the psychological recovery of the survivors of the Mount Semeru eruption. Methods of self-motivation and play therapy are used to achieve these goals. The stages of implementing this activity include preparation, program implementation, and evaluation. The preparation phase of the team conducts a needs analysis to identify problems, coordinate with various parties and map out infrastructure. The implementation phase includes socialization, preparation of materials and training programs. The evaluation stage is carried out to measure the success of the service program implementation. The results showed that the activities carried out at SDN 1 and SDN 2 Supiturang on 5-6 August 2022 ran smoothly. Most of the participants were children who followed enthusiastically from the beginning to the end of the activity. At the evaluation stage, it was known that in teaching and learning activities the children were very enthusiastic and emotional expression went well after this service activity was held.